Eksperyment jednopodmiotowy – charakterystyka metody i jej zastosowanie w naukach o edukacji - Trusz, Sławomir (Studia Edukacyjne, 2021)
A single-subject experiment, also known as quantitative case study or n = 1 research design, is an extraordinary but rarely used research method when it comes to education. This method combines precision of experiment with depth of qualitative analyses carried out on the basis of data obtained from a single subject under standardized observation. The paper presents formal characteristics, hypo[1]thesis verification conditions as well as strengths and weaknesses of the five single-subject experiment schemas, i.e.: (1) AB design, (2) reversal design ABAB, (3) multiple baseline design, (4) alternating treatment design, and (5) changing criterion design. Furthermore, graphic and non-graphic methods of testing hypotheses on causal relations between independent and outcome variables appropriate for the single-subject experiment are discussed.